Evaluation of AQP4 functional variants and its association with fragile X-associated tremor/ataxia syndrome - Elias-Mas, Andrea; Potrony, Miriam; Bague, Jaume; Cutler, David J.; Alvarez-Mora, Maria Isabel; Torres, Teresa; Barcos, Tamara; Puig-Butille, Joan Anton; Rubio, Marta; Madrigal, Irene; Puig, Susana; Allen, Emily G.; et al. (Frontiers in Aging Neuroscience, 2023)
Introduction Fragile X-associated tremor/ataxia syndrome (FXTAS, OMIM# 300623) is a late-onset neurodegenerative disorder with reduced penetrance that appears in adult FMR1 premutation carriers (55–200 CGGs). Clinical symptoms in FXTAS patients usually begin with an action tremor. After that, different findings including ataxia, and more variably, loss of sensation in the distal lower extremities and autonomic dysfunction, may occur, and gradually progress. Cognitive deficits are also observed, and include memory problems and executive function deficits, with a gradual progression to dementia in some individuals. Aquaporin 4 (AQP4) is a commonly distributed water channel in astrocytes of the central nervous system. Changes in AQP4 activity and expression have been implicated in several central nervous system disorders. Previous studies have suggested the associations of AQP4 single nucleotide polymorphisms (SNPs) with brain-water homeostasis, and neurodegeneration disease. To date, this association has not been studied in FXTAS. Methods To investigate the association of AQP4 SNPs with the risk of presenting FXTAS, a total of seven common AQP4 SNPs were selected and genotyped in 95 FMR1 premutation carriers with FXTAS and in 65 FMR1 premutation carriers without FXTAS. Results The frequency of AQP4-haplotype was compared between groups, denoting 26 heterozygous individuals and 5 homozygotes as carriers of the minor allele in the FXTAS group and 25 heterozygous and 2 homozygotes in the no-FXTAS group. Statistical analyses showed no significant associations between AQP4 SNPs/haplotypes and development of FXTAS. Discussion Although AQP4 has been implicated in a wide range of brain disorders, its involvement in FXTAS remains unclear. The identification of novel genetic markers predisposing to FXTAS or modulating disease progression is critical for future research involving predictors and treatments.